Goldfish Group Choice : Tests of the Ideal Free Distribution and Matching Theory. - Hedquist, Chelsea B. (My University, 2009)
The ideal free distribution theory has been used to explain group foraging behavior between two or more locations. Group foraging behavior occurs when organisms move from one location to another to access some available resource (e.g., food patch). The purpose of the present study was to investigate a group of common goldfish would also demonstrate undermatching, like other animals and humans have, when using three different variable time schedules of reinforcement.
Color poster with text, images, table, and graph (Spring 2009)
Keywords: Reinforcement (Psychology); Goldfish--Behavior; Goldfish--Feeding and feeds; Goldfish--Schooling; Resource allocation; Posters